HYGIENIC ASSESSMENT OF PHYSICAL DEVELOPMENT INDICATORS AND MORBIDITY IN POST-TERM INFANTS - Ortiqov Bobomurod Baymamatovich; Hasanova Sayyora Shomurot qizi (Scholar Express Journals, 2025)
This study is devoted to examining the physical development indicators and morbidity rates among post-term infants. Based on the analysis conducted among 94 children, it was found that 61.7% were boys and 38.3% were girls. Significant deviations were observed in anthropometric parameters of height and weight: 59% of children showed minimal deviations, while 23% had maximal deviations. According to the data on morbidity, the most common diseases were respiratory tract infections (60%) and rickets (56%). In addition, gastrointestinal disorders, anemia, allergic, and congenital diseases were also identified. The results of the study indicate that the level of physical development and susceptibility to diseases in post-term infants are directly related to the quality of nutrition and care conditions.
Keywords: post-term infants; anthropometric indicators